Retroviral vector particles displaying the antigen-binding site of an antibody enable cell-type-specific gene transfer. - Chu, T H (1995)
Retroviral vectors are the most efficient tool for stably introducing genes into vertebrate cells. However, their use is limited by the host range of the retrovirus from which they are derived. To alter the host range, we recently constructed retrovirus vector particles, derived from spleen necrosis virus, that display a single-chain antigen-binding site of an antibody (scA) on the viral surface (T.-H. T. Chu, I. Martinez, W. Sheay, and R. Dornburg, Gene Ther. 1:292-299, 1994). Using a hapten (2,4-dinitrophenol) model system, we showed that such particles are competent for infection. In this study, we repeated our experiments using an scA directed against a cell surface protein expressed on various human carcinoma cell lines. We found that such scA-displaying particles can efficiently infect human cells that express the corresponding antigen. Particles with wild-type spleen necrosis virus envelope are minimally infectious on such cells. The addition of the original monoclonal antibody to the viral vector particle solution prior to infection inhibited infection. This competition assay showed that the infection is mediated by the antibody moiety and, therefore, is antibody specific. These data indicate that retroviral vectors with antibody-envelope fusion proteins may be a valuable tool for selectively introducing genes into any target cell.